Study of fungal diseases on Swertia chirayita from cultivated fields of Dolakha district, central Nepal - Thapa, Rabindra; Jha, Sanjay Kumar (Our Nature, 2022)
Swertia chirayita is a medicinally and economically important herb of the family Gentinaceae. It is one of the highly traded, traditionally important medicinal plants. Fungal Pathogens corrupt the quality and amount of Swertia chirayita development, and production and cause terrible well-being of plants as well as monetary problem to the traders. This study was carried out to identify some diseases associated with S. chirayita cultivated fields in Bigu, Khartal, and Boch regions of Dolakha district. The samples were collected from selected sites and cultured on Potato Dextrose Agar media for fungal pathogens. During the investigation, five species of fungal pathogens were identified. Alternaria alternata, Colletotrichum gleosporioides and Curvularia sp. were isolated from leaf. They caused Alternaria leaf spot, Colletotrichum leaf blight, and Curvularia leaf spot. Similarly, stem possesses canker disease and root had root canker, Fusarium oxysporum causing Fusarium wilt, Rhizoctonia sp. causing Rhizoctonia root rot. The presence of illnesses in S. chirayita shows the need for proper plant care.